An analysis of volumes, prices and pricing trends of the pediatric antiretroviral market in developing countries from 2004 to 2012. Issue 1 (December 2016) - Lee, Janice; Sagaon Teyssier, Luis; Dongmo Nguimfack, Boniface; Collins, Intira; Lallemant, Marc; Perriens, Joseph; Moatti, Jean-Paul
Abstract Background The pediatric antiretroviral (ARV) market is poorly described in the literature, resulting in gaps in understanding treatment access. We analyzed the pediatric ARV market from 2004 to 2012 and assessed pricing trends and associated factors. Methods Data on donor funded procurements of pediatric ARV formulations reported to the Global Price Reporting Mechanism database from 2004 to 2012 were analyzed. Outcomes of interest were the volume and mean price per patient-year ARV formulation based on WHO ARV dosing recommendations for a 10 kg child. Factors associated with the price of formulations were assessed using linear regression; potential predictors included: country income classification, geographical region, market segment (originator versus generic ARVs), and number of manufacturers per formulation. All analyses were adjusted for type of formulations (single, dual or triple fixed-dose combinations (FDCs)) Results Data from 111 countries from 2004 to 2012 were included, with procurement of 33 formulations at a total value of USD 204 million. Use of dual and triple FDC formulations increased substantially over time, but with limited changes in price. Upon multivariate analysis, prices of originator formulations were found to be on average 72 % higher than generics (p  < 0.001). A 10 % increase in procurement volume was associated with a 1 % decrease (p  < 0.001) in both originator and generic prices. The entry of one additional manufacturer producing a formulation was associated with a decrease in prices of 2 % (p  < 0.001) and 8 % (p  < 0.001) for originator and generic formulations, respectively. The mean generic ARV price did not differ by country income level. Prices of originator ARVs were 48 % (p  < 0.001) and 14 % (p  < 0.001) higher in upper-middle income and lower-middle income countries compared to low income countries respectively, with the exception of South Africa, which had lower prices despite being an upper-middle income country. Conclusions The donor funded pediatric ARV market as represented by the GPRM database is small, and lacks price competition. It is dominated by generic drugs due to the lower prices offered and the practicality of FDC formulations. This market requires continued donor support and the current initiatives to protect it are important to ensure market viability, especially if new formulations are to be introduced in the future.